A Synchronous Online Social Work PhD Program: Educational Design and Student/Faculty Response. Issue 4 (20th October 2019) - Myers, Dennis; Singletary, Jon; Rogers, Rob; Ellor, Jim; Barham, Sidney
ABSTRACT: Faculty and students evaluate the curriculum design and delivery of a synchronous online PhD program in social work that prepares scholar-practitioners in social work research, education, and organizational practice. The designers envision a collaborative community of scholars and leaders nurtured by a cohort-based, sequenced curriculum, and intentional faculty mentoring. This teaching and learning platform provides an opportunity to engage with a globally diverse population of doctoral students while fostering both relationships and quality learning outcomes. Educational design and pedagogical features of the program are described and analyzed through the collaborative thinking and learning platform of the Community of Inquiry (CoI) model's interdependent elements–teaching, cognitive, and social presence. Eighteen students and ten faculty evaluated the strengths and limitations of the online program across each dimension of the model through student course evaluations, focus-group reflections, and qualitative faculty survey data. Student and faculty respondents specified the benefits of synchronous presence across all three dimensions. They also identified significant barriers, particularly in the areas of teaching and social presence. Implications and recommendations are based on a review of findings that inform pedagogical decisions and design options for online PhD education in social work.